Comparison of the effect of thermal stresses on tooth-colored posts, cores and tooth structures by finite element analysis - Ferhan Egilmez; Levent Nalbant (Cumhuriyet Dental Journal, 2012)
Objectives: The aims of this study were to analyze the influence of cold heat flow in all ceramic crown material, composite core, zirconium and glass fiber reinforced composite post materials, resin based luting cement and root dentin; and to compare these two tooth-colored post systems about their temperature and thermal stress distributions. Materials and Methods: A 3-dimesional finite element model of maxillary left canine tooth was constructed. All ceramic crown, composite core, tooth dentin, post and bone were modeled. In the first part of this study, initial body temperature was assumed to be 36.5°C and the outer temperature was reduced to 0°C for 5 secs. In the second part, the thermal stress was calculated as a result of temperature change. For the analysis, 7 nodes of the finite element model were selected and heat flow, temperature and thermal stres on these nodes were evaluated. Results: Mean temperature value was 15.75 °C for GFRC post model and 15.47 °C for Zr post model. The maximum von Mises stress was obtained at the node C in both post systems. In general, thermal stress was observed on the cervical part of all-ceramic crown and there was an interface between root dentin-composite core and post material. The temperature gradient of the GFRC post was smaller than that of the zirconia post.Conclusions: Within the limitation of this study, zirconia posts produced greater stress than GFRC posts. Temperature changes had more effect on the post-cement interface and cervical areas than on the other areas.